Homestay Services for Tourism Industry - Dahal, Madhav Prasad (Tejganga Darpan, 2024)
Home stay is a kind of tourism development model which provides local lifestyle, culture and tradition to the visitors. At present situation, it is impossible to maintain sustainable home stay tourism unless the visitors are satisfied. To overcome this condition, this research aims to find out the link between tourists’ satisfaction and sustainable Homestay. This article attempts to assess the economic contribution of Homestay of investigating area on the descriptive and exploratory research design. Data collection for this research work homestays were selected randomly from Panauti municipality and Bethanchok rural municipality of Kavrepalnchok district. The result based on statistics reflects the significant increase in income and expenditure of home stay managers in the study area. The savings and credits behavior of the local people will be evaluated through this research. This research will be focused on two aspects of sustainable home stay tourism i.e. tourism for economic sustainability and tourist pleasure. The respondents for this research have been taken from different cultural and religious backgrounds. Finally, the researcher believe that this study includes a meaningful conclusion, theoretical and managerial consequences as well as future research directions for the contribution of home stays to promote tourism industry. The result of this study assists for the policy makers and local government to allocate the budget for enhancing the local tourism industry with the help of home stay services